2022
DOI: 10.3389/fbioe.2022.913791
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Target for Diabetic Vascular Damage: High Glucose-Induced Monocyte Extracellular Vesicles Impair Endothelial Cells by Delivering miR-142-5p

Abstract: Endothelial dysfunction is a key accessory to diabetic cardiovascular complications, and the regulatory role of the extracellular vesicles (EVs) from the innate immune system is growing. We tested whether EVs derived from high glucose-induced monocytes could shuttle microRNAs and impair endothelial cells. EVs from high glucose- and basal glucose-treated THP-1 cells (HG-THP-1 EVs and BG-THP-1 EVs) were isolated and identified. After coculture with THP-1 EVs, human umbilical vein endothelial cells (HUVECs) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Particularly, hypoxia and hyperglycemia not only increase sEVs release but also modify its content, affecting neighboring cells [16,17]. This phenomenon has been associated with the promotion of critical physiological and pathological processes such as autophagy, cell migration, angiogenesis, and endothelial dysfunction [18][19][20]. Fitting with this, we demonstrate how HG exposure significantly increases sEVs release from ARPE-19 cells similarly to other oxidative challenges [9,15,16,[21][22][23].…”
Section: Discussionsupporting
confidence: 61%
“…Particularly, hypoxia and hyperglycemia not only increase sEVs release but also modify its content, affecting neighboring cells [16,17]. This phenomenon has been associated with the promotion of critical physiological and pathological processes such as autophagy, cell migration, angiogenesis, and endothelial dysfunction [18][19][20]. Fitting with this, we demonstrate how HG exposure significantly increases sEVs release from ARPE-19 cells similarly to other oxidative challenges [9,15,16,[21][22][23].…”
Section: Discussionsupporting
confidence: 61%
“…Besides, miR-34a was elevated in renal tissue of diabetic kidney disease (DKD) and increased the levels of ROS and inflammation in human renal glomerular endothelial cells by inhibiting the expression of autophagy-related gene 4B (ATG4B), which might contribute to the pathogenesis of DKD [ 97 ]. Notably, miR-142-5p delivered by high glucose-induced monocyte extracellular vesicles reduced migration and increased ROS production in HUVECs and inhibition of miR-142-5p alleviated inflammation in T1DM mice aortas [ 98 ]. In a word, these studies suggest that inhibition or activation of microRNAs could be a potential adjuvants to diabetic vascular therapy.…”
Section: Mechanisms Of Ros-induced Endothelial Dysfunction In Diabeti...mentioning
confidence: 99%
“…Moreover, researchers revealed that exosomal miR-142-5p is participated in the pathogenesis of vascular damage by targeting IL-1β. 238 Obesity: miRNA can be a vital regulator for the pathogenesis of obesity. Zhang et al 239 performed RNA sequencing and found that miR-342-3p and its host gene Evl, which are co-expressed in the hypothalamic arcuate nucleus neurons, are increased in the brain and adipose tissues of mice with diet-induced obesity.…”
Section: The Role Of Mirnas In Metabolic Diseasementioning
confidence: 99%